The Construction of Santri's Self-Control and Religiosity: The Role of Parents, Kiai, and Peers - Maulana Achsan Al Farisi; Riany, Yulina Eva; Yuliati, Lilik Noor (Journal of Educational, Health and Community Psychology, 2025)
The dynamics of life in Islamic boarding schools (pesantren), particularly concerning self-control and religiosity, are increasingly relevant amid evolving educational and social contexts. As santri (students) navigate a blend of religious discipline and modern influences, understanding the factors that shape their character becomes essential. This study investigates the roles of parental interaction, kiai (religious leader) communication, and peer attachment in influencing santri’s self-control and religiosity. Using a quantitative approach, data were collected from diploma- to bachelor-level santri aged 18–23 through Cluster Random Sampling and Purposive Sampling techniques. A total of 24 indicators were employed across validated instruments: Adolescent-Reported Parenting Items (α = 0.85), Interpersonal Communication Motives (α = 0.92), Inventory of Parent and Peer Attachment (α = 0.81), Self-Control Scale (α = 0.85), and the Religiosity Among Muslims scale (α = 0.98). Results show that strong parental interaction significantly enhances both self-control and religiosity, highlighting the critical role of family involvement in santri character formation. Communication with kiai also positively affects religiosity, reinforcing the value of spiritual guidance. These findings offer important implications for educators, parents, and pesantren leaders in developing strategies to support santri character development amidst shifting social landscapes.